The Modern State and Historical Aspects of Homeopathy as a Scientific and Educational Discipline in Ukraine - Olena Olexandrivna Gaidukova; Svitlana Valentynivna Oliinyk; Evgen Yakovych Nikolenko; Kira Vitaliivna Vovk; Olha Olexandrivna Vlasenko (Journal of Global Pharma Technology, 2020)
The problem-targeted analysis of the modern homeopathy structure is carried out. The state of the modern regulatory and legal framework concerning regulation of the homeopathic method of treatment as the basis of the legal mechanism in state management of this branch is analyzed. The historical aspects of homeopathy are generalized, the analysis of homeopathic doctors’ activity legal regulation in Ukraine is carried out, and also issues of their education are covered. The results of scientific achievements are presented and their role in the formation of the evidence base for the homeopathic method of treatment is outlined. The problems of homeopathic medicine, pharmacy and science are covered. Key words: homeopathy, data of scientific literature, legal regulation, homeopaths, pharmacological studies.